Present and future of telemedicine for pediatric care: an Italian regional experience - Gianvincenzo Zuccotti; Valeria Calcaterra; Andrea Foppiani (BMC, 2023)
Abstract Telemedicine has been recognized as an integral part of the National Health Service in Italy. Telemedicine can be adopted in the diagnostic therapeutic assistance pathway and in individual assistance plans. In the region of Lombardy, home care models from the perspective of the project of a public virtual hospital have been introduced. A regional operational center was proposed to ensure continuing care utilising organizational and technological solutions to deliver healthcare services remotely, with high quality standards, a positive economic impact and user friendly services for both the user and the professional. In the field of pediatrics telemedicine was also introduced at the Vittore Buzzi Children' Hospital, in Milan, the capital of the region of Lombardy. These included routine pediatric hospital activities and innovative programs, such as early discharge, telecardiology, online supervised exercise training and preventive healthcare. Telehealth represents the evolution of health care delivery systems to adapt to new technology and the needs of the pediatric population, offering a strategic system to invest in children's health.